New multi-phase flow metering technology available for industrial measuring units in the oil and gas industry - Casimiro, R; Henry, M; Tombs, M; Kroshkin, A; Lishchuk, A (Neftyanoe Khozyaistvo, 2014)
This paper describes a new commercial multi-phase metering system combining Coriolis mass flow with water cut metering. The NetOil&Gas; measurement skid, utilizing this technology, has been developed and certified as an industrial multi-phase flow meter. Industrial stationary and mobile units MERA-MR, based on the NetOil&Gas; flow meter, have brought this state-of-the-art technology to field metering practice. The results from a number of laboratory and field trials have confirmed that this technology is applicable in the oil and gas industry. The first commercial procurement contracts have now been signed. References